The experience of aggression by female teachers in the workplace - D.S. van der Merwe; C.P.H. Myburgh; M. Poggenpoel (AOSIS, 2015)
South Africa is a country with exceptionally high levels of frustration and trauma. Research shows that a third of all people in South Africa are exposed to some kind of violence. This causes insecurity and fear, which creates high levels of stress. High stress levels fuels aggression in the workplace. It was observed that female teachers often experience aggression in the workplace. This has a negative effect on their overall sense of well-being as well as their mental health. A purposive sample was selected through two private schools in Gauteng, South Africa, and consisted of eight female teachers. Data was collected by means of in-depth phenomenological interviews, field notes, naive sketches and observation. One central question was posed to the purposefully selected participants: What is your experience of aggression in your workplace? Thematic coding was used to analyse the data. Three themes were identified: different perceptions influenced female teachers' experience of aggression; the pressure in the school system formed an integral part of the experience of aggression and the experienced effect of aggression on the female teachers.